(untitled) (Journal of Nematode Morphology and Systematics, 2012)
One new and one known species of the genus Mesorhabditis, and one known species each of the genera Bursilla and Cruznema are described from natural areas in the South of the Iberian Peninsula. M. carmenae sp. n. is characterized by having body 440-514 μm long in females and 494-618 μm in males, stoma 17-21 μm long and 4 μm wide, vulva very posterior (V = 83-85), distance vulva-anus 2.8-3.4 times female tail, female tail conical (18-20 μm, c = 24.4-27.1, c’ = 0.9-1.1) with acute terminal part, phasmid near to anus, male tail conical (20-30 μm, c = 17.4-28.3, c’ = 1.0-1.6), spicules 50-54 μm long and fused in their distal part, gubernaculum 24-27 μm long, and bursa open anteriorly with ten (2+4+4) pairs of genital papillae. Descriptions, measurements and illustrations, including SEM photographs, are provided for the four species.